Conditional control of dendritic cell factor 1 expression by a tetracycline-inducible system - Yan, H; Huang, C; Yang, M; Guo, J; Wang, J; Feng, R; Wen, T (Cellular and Molecular Biology, 2015)
Dendritic cell factor 1 plays important roles in neural stem cells differentiation and in glioma cells proliferation, migration, and invasion. Here, we used a tetracycline-inducible system that regulates the expression of Dendritic cell factor 1 in glioma cells. We constructed two tet-inducible vectors, pTRE-EGFP-DCF1 and pTRE-LJM1-DCF1, by modifying the promoter PCMV. In the absence of tetracycline or doxycycline, the expression of Dendritic cell factor 1 in cells co-transfected with pTRE-EGFP-DCF1 or pTRE-LJM1-EGFP-DCF1 and ptTS-Neo was suppressed through binding of the tetracyline-controlled transcriptional suppressor to tetracycline response element, and the suppression was released by the addition of doxycycline. Our work has laid foundations for potential clinical application of cancer therapy in realizing artificial regulation of gene.